2005
DOI: 10.1016/j.jasms.2005.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and optimization of electron capture dissociation efficiency in fourier transform ion cyclotron resonance mass spectrometry

Abstract: Electron capture dissociation (ECD) efficiency has typically been lower than for other dissociation techniques. Here we characterize experimental factors that limit ECD and seek to improve its efficiency. Efficiency of precursor to product ion conversion was measured for a range of peptide (ϳ15% efficiency) and protein (ϳ33% efficiency) ions of differing sizes and charge states. Conversion of precursor ions to products depends on electron irradiation period and maximizes at ϳ5-30 ms. The optimal irradiation pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 35 publications
6
47
0
Order By: Relevance
“…We have previously demonstrated that AI-ECD of IgA1 HR distinguished between a single population and an isobaric mixture of differentially glycosylated HR peptides (20). However, fragmentation by use of ECD is less efficient than the more traditional collision-induced dissociation in the conversion of parent ions to fragments (ϳ30 versus Ͼ70% conversion) (40). As such, a small subpopulation of isobaric IgA1 HR O-glycoforms with sites of Gal deficiency as indicated by the N-terminal fragments would not be observed in the presence of a dominant single population.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that AI-ECD of IgA1 HR distinguished between a single population and an isobaric mixture of differentially glycosylated HR peptides (20). However, fragmentation by use of ECD is less efficient than the more traditional collision-induced dissociation in the conversion of parent ions to fragments (ϳ30 versus Ͼ70% conversion) (40). As such, a small subpopulation of isobaric IgA1 HR O-glycoforms with sites of Gal deficiency as indicated by the N-terminal fragments would not be observed in the presence of a dominant single population.…”
Section: Discussionmentioning
confidence: 99%
“…Gated ion trapping was used without cooling gas. For ECD experiments, a variable delay period (typically 50 ms at 10 V trapping voltage) was used to optimize ion magnetron motion phase [41]; a 3-mm-diameter electron beam (1-100 ms) was then injected into the ICR trap, followed by an electron clean-up event (100 ms) [40,42]. The cathode potential during electron injection was Ϫ5 V and kept at ϩ10 V otherwise.…”
Section: Tandem Mass Spectrometrymentioning
confidence: 99%
“…Accelerating grid voltage was at ϩ5 V during electron injection and at Ϫ200 V otherwise. A multiple-pass electron injection regime was used (transfer octopole DC offset Ϫ60 V) [40,42]. For AI-ECD experiments, precursor ions were activated by CO 2 IR laser irradiation (50 -100 ms at ϳ25 W continuous-wave laser output power; the laser was equipped with a 2.5ϫ beam expander to improve overlap with the ion cloud) before electron injection [39].…”
Section: Tandem Mass Spectrometrymentioning
confidence: 99%
See 1 more Smart Citation
“…The fragmentation efficiency in SORI-CAD is, as expected, higher (22% for NAD and 40% for NADP under the conditions used) than that in ECD (11% for NAD and 12% for NADP). Efficiencies were calculated based on the total product ion abundance divided by the initial precursor ion abundance (measured in a separate experiment), as proposed by McFarland et al [58].…”
Section: Ecd and Sori-cad Ms/ms Of Nad And Nadp Complexed With Ca 2ϩmentioning
confidence: 99%